Private wealth and planned early retirement: A panel data analysis for the Netherlands, 1994 - 2009 - Raun van Ooijen; Mauro Mastrogiacomo; Rob Euwals (Institute for the Study of Labor (IZA), 2010)
We study the causal relation between private wealth and retirement age. We propose two estimation strategies based on expected retirement age. The outcome variable is observed repeatedly over time. We correct first for the unobserved heterogeneity in the disutility of work by using panel data techniques. Next, we exploit information on expected wealth accumulation in order to identify the unexpected component in wealth accumulation. In line with the literature we find a small but significant effect of private wealth on planned early retirement.
Keywords: C23; J26; 330; early retirement; private wealth; subjective retirement expectations